Profile of Pre-service Physics Teachers' Representational Fluency on Electrostatic Concept - Handayani, Wahyuni; Masrifah, ‎ (KnE Social Sciences, 2024)
Science teachers have to master representational to communicate and be aware of the students’ difficulties in understanding science concepts. This study aims to determine representational fluency as part of science communication skills in pre-service physics teachers. This study uses descriptive analysis techniques based on the percentage. The research subjects are 50 pre-service physics teachers aged between 19 and 22 years. This study was conducted at the Study Program of Physics Education of a college in Maluku. How fluent is a pre-service physics teacher in representing the concept of electrostatic was measured using 15 valid and reliable representational fluency multiple choice test that includes four component of representational fluency: constructing single representation, constructing multiple representation, translating between representation and reviewing single representation. The findings of the present study indicate that although students had started to learn concepts of electrostatic their representational fluency is still low. The preservice teachers’ rate of giving correct answers to the test items varies between 8% and 48%. The mean score of the pre-service teachers was found to be 4.06. Keywords: representational fluency, electrostatic